Probiotic characterization of Limosilactobacillus fermentum BGHV110 strain and its influence on innate immune response in Caenorhabditis elegans - Dinić, Miroslav; Popović, Nikola; Radojević, Dušan; Djokić, Jelena (Archives of Pharmacy, 2023)
Probiotic lactobacilli exhibit the potential to promote health benefits for the host. Thanks to its numerous beneficial effects on human health, Limosilactobacillus fermentum stood out as an excellent candidate for the development of commercial probiotic preparations aiming to prevent community-acquired infections. In this study, several in vitro tests, including biofilm formation assay, assessment of antibiotic susceptibility, survival in simulated gastrointestinal tract conditions and attachment to intestinal Caco-2 cells, were used to estimate the safety and probiotic potential of L. fermentum BGHV110 strain. Additionally, Caenorhabditis elegans was used as an in vivo model system for the evaluation of L. fermentum BGHV110 influence on the host’s innate immune response. The results revealed that L. fermentum BGHV110 strain showed an excellent capability to survive harsh conditions of the gut, to attach to intestinal Caco-2 cells and to stimulate conserved p38 MAPK immunity pathway and expression of the clc-1 claudin-like gene and antimicrobial peptides in C. elegans in order to enhance the immune response against pathogens. Finally, L. fermentum BGHV110 showed no virulence traits and susceptibility to tested antibiotics, confirming its safety status which enables it to be applied as a future probiotic.
Keywords: Limosilactobacillus fermentum; probiotic; innate immune response; gastrointestinal tract; Caenorhabditis elegans